Analisis Kualitas Butir Soal dan Abilitas Siswa pada Asesmen Madrasah Ibtidaiyah dengan Rasch Model - Jannah, Raudhatul (Jurnal Didaktika Pendidikan Dasar, 2024)
Item analysis is very important because it can help teachers to find out whether the measurement tools given to students can measure students' abilities. Some things that need to be analyzed from the questions and student learning outcomes are the suitability of the items, the level of difficulty, and also the abilities of students. So this article will discuss it. This research is a quantitative descriptive evaluative research. The research subjects were students' answers to questions on Madrasah Assessment in Social Sciences. Data analysis of student learning outcomes was carried out using the Winstep 3.73 application. The results of this study note that the IPS Assessment questions have compatibility with the fit characteristics because they can meet at least one of the three criteria that have been set. Then the questions have varying levels of difficulty because three questions fall into the category of too difficult and too easy. Furthermore, if seen from the student's ability to answer the questions, abnormal patterns were found, so the teacher needs to review the student's learning outcomes.